PEMBELAJARAN PENDIDIKAN JASMANI BERBASIS MULTIASPEK, KOLABORATIF, DAN SINTESIS KEUNGGULAN SUMBER BELAJAR - Agus Kristiyanto (Jurnal Cakrawala Pendidikan, 2011)
Abstract: The Learning of Physical Education Based on Multi-Aspect Competence, Collaboration, and Synthesis of Learning Resource Advantages. This study aims to: (1) sharpen the pragmatic aspects of a model for briefing physical education student-teachers on their competence; (2) improve the institutional policy concerning ways of briefing them on their competence in physical education oriented to the present conditions; (3) develop the substance of the physical education microteaching; (4) improve the recognition of expertise from peers; and (5) map the networking of the partner institutions. This study employed a combination of methods consisting of a library study, descriptive survey, and action research. The data were collected through questionnaires, in-depth interviews, and focus group discussions. The findings show that the briefing model should comprise (1) multi-aspect competence, i.e. pedagogic, personal, professional, and social aspects; (2) collaboration by involving other relevant and competent parties; and (3) learning-resource sharing by making use of advantages of learning resources in the campus and partner schools. Keywords: learning of physical education, multi-aspect competence, collaboration, learning-resource sharing